Respon Pertumbuhan Tanaman Seledri (Apium Graviolens L) Dengan Sistem Vertikultur Pada Jenis Pupuk Organik dan Hayati - Sudirman Sudirman; Antar Sofyan; Jumar Jumar (Agroekotek View, 2021)
Celery (Apium graveolens L) is included in the Apiacean family and is a vegetable commodity that is widely used for flavoring and garnishing dishes. Celery seeds are also used as a spice and flavoring and the seed oil extract has medicinal properties. Glucoside apigenin7apiosiglucoside is a scent producer of celery leaves (Tim Prima Tani, 2011). and biological fertilizer (Trichoderma Koningi) as an alternative mixture of soil media with different treatment ratios. This research method uses one-factor RAK with 3 treatments and 8 replications, the research was carried out in the pilot area of Mr. Ir. Antar Sofyan, MP which took place in September 2019 - November 2019 The results showed that P2 treatment, namely Bokashi (Trichoderma Koningi) Biological Fertilizer, significantly affected the growth of celery plants (Apium graveolens L) with the verticulture system in all observed parameters, the highest plant height with an average of 9.67 a, the most number of stems ak with an average of 6.38, the highest number of tillers with an average of 8.33 tillers, and fresh weight with a productive number (7.5 g).